Does increased heat resistance result in higher susceptibility to predation? A test using Drosophila melanogaster selection and hardening. (15th May 2017) - Hangartner, S.; Dworkin, I.; DeNieu, M.; Hoffmann, A. A.
Abstract: Heat resistance of ectotherms can be increased both by plasticity and evolution, but these effects may have trade‐offs resulting from biotic interactions. Here, we test for predation costs in Drosophila melanogaster populations with altered heat resistance produced by adult hardening and directional selection for increased heat resistance. In addition, we also tested for genetic trade‐offs by testing heat resistance in lines that have evolved under increased predation risk. We show that while 35/37 °C hardening increases heat resistance as expected, it does not increase predation risk from jumping spiders or mantids; in fact, there was an indication that survival may have increased under predation following a triple 37 °C compared to a single 35 °C hardening treatment. Flies that survived a 39 °C selection cycle showed lower survival under predation, suggesting a predation cost of exposure to a more severe heat stress. There was, however, no correlated response to selection because survival did not differ between control and selected lines after selection was relaxed for one or two generations. In addition, lines selected for increased predation risk did not differ in heat resistance. Our findings suggest independent evolutionary responses to predation and heat as measured in laboratory assays, and no costs of heat hardening on susceptibility to predation.